Penguatan Literasi Bahasa Berbasis Budaya Lokal di Sekolah Dasar: Kajian Pustaka - Faiz Romli; Abdul Wachid Bambang Suharto (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
The low language literacy skills of elementary school students in Indonesia remain a chronic problem that conventional policies have failed to resolve. Previous studies have tended to focus on the technical aspects of reading without considering the local cultural context that is closely tied to children’s daily lives. This article aims to examine the concepts, implementation, impacts, challenges, and strategies for strengthening language literacy based on local culture in elementary schools. The research employs a qualitative approach using library research. The data sources consist of 22 literature sources, including journal articles, conference proceedings, books, theses, and policy documents published over the past ten years (2016–2026) that discuss language literacy and local culture in elementary schools, analyzed using content analysis techniques. The research findings indicate that local culture-based language literacy in elementary schools enhances students’ reading motivation, text comprehension, cultural pride, and critical thinking. Its implementation involves the use of folktales, traditional games, and digital media rooted in local wisdom. The main challenges are the limited availability of engaging local reading materials, a lack of teacher training, and difficulties faced by bilingual students. The study’s conclusion emphasizes that this approach requires synergy among teachers, parents, the community, and policies grounded in local wisdom. The novelty of this research lies in its cross-regional, cross-grade-level, and cross-media synthesis, an integrated approach not previously undertaken by prior studies.